Cover Feature: Recent Advances of Biphenylene: Synthesis, Reactions and Uses (Eur. J. Org. Chem. 18/2019). Issue 18 (7th May 2019) - Takano, Hideaki; Ito, Takeharu; Kanyiva, Kyalo Stephen; Shibata, Takanori
Abstract : The Cover Feature shows biphenylenes, unique, stable compounds that have 12π‐electron antiaromatic system. This feature makes them attractive synthetic targets as well as substrates for the preparation of polycyclic compounds initiated by C–C bond cleavage of the cyclobutadiene core. This minireview shows the charm of biphenylene skeleton from the point of synthesis, reactions, and uses. More information can be found in theMinireview by T. Shibata et al.